From Kitchen to Clinic: A PRISMA-Based Systematic Review of Culinary-Induced Food Poisoning in Mass Feeding Programs and Its Mitigation in Cookery Science - Diyan Putranto; Marhanani Tri Astuti; Fransiscus Amonio Halawa (Journal Management SMC, 2026)
Background: The Indonesian Makan Bergizi Gratis (MBG) program aims to combat child malnutrition through mass school feeding. However, transitioning from domestic to industrial-scale production introduces significant "Large-scale Food Hazards" where culinary technique failures serve as primary toxicological independent variables. Objective: This study systematically evaluates the nexus between professional cookery techniques and clinical poisoning outcomes to propose a "Safe-Cookery Framework" for the MBG supply chain. Methodology: Following PRISMA 2020 guidelines, a systematic review was conducted across Scopus, ScienceDirect, PubMed, and Sinta databases. A corpus of 20 high-impact articles (2014–2024) was analyzed using a "Process-Analytical Approach" to map Culinary Failure Points (CFP). Results: Findings identify three critical "Fault Lines": (1) thermal lag in large-batch processing (pot volumes >100L) leading to pathogen survival in "cold cores"; (2) improper cooling of starches triggering heat-stable Bacillus cereus toxin production; and (3) a logistical "Golden Hour" breach where transit >1 hour facilitates Clostridium perfringens multiplication. Chemical risks include pesticide residue accumulation and heavy metal leaching from non-food-grade aluminum cookware. Conclusion: Mass food poisoning in institutional catering is a predictable outcome of specific technical failures. Policy recommendations include mandating unidirectional kitchen flows, enforcing a 5-km delivery radius, and elevating kitchen leads to "Managerial Toxicology" certified Executive Chefs.